Pengukuran Tingkat Kesiapan Implementasi E-Learning di Politeknik Negeri Jakarta - Warsuta, Bambang; Muharram, Asep Taufik; Yusdisti, Iga; Jasmine, Syahda Afallia (Jurnal Teknologi Terpadu, 2021)
Politeknik Negeri Jakarta (PNJ) is anticipated to be an Asia-Class Polytechnic. The strategic issue of PNJ development to be transformed into an Asia-Class Polytechnic is the implementation of â€œDigital Transformationâ€ for learning and servicing. One of the forms of this digital transformation is e-learning. The success of e-learning is influenced by how much the institution has prepared to utilize information technology in the learning process. This research uses an action research design with a questionnaire instrument based on an established model. Aydin and Tasci Model, adapted for an educational institution, is utilized for the preparedness evaluation. The measurement scale used in the model is a Likert scale (1-5). Aydin and Tasci divided the scale into four assessment intervals, which is not ready, needs much work (index 1-2,59); not ready, needs some work (index 2,6-3,39); ready, but needs a few improvements (index 3,4-4,19); ready go ahead (index 4,2-5). The result with a score of 4,16 indicates that PNJ is ready to implement e-learning with slight improvement, which is related to self-development and innovation.